2018
DOI: 10.1177/1354816618803272
|View full text |Cite
|
Sign up to set email alerts
|

Valuing forest park attributes by giving consideration to the tourist satisfaction

Abstract: Despite the economic valuation of forest park resources has triggered a great deal of interest to the research community and park management, up to now no attention has been paid to the effect of psychological factors such as tourist satisfaction, which could potentially play a considerable role in contributing to the park resource valuation. This article attempts to fill this niche by carrying out a study on the economic valuation of the Xian-Ren-Tai National Forest Park in China, taking consideration of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 72 publications
4
10
0
Order By: Relevance
“…This inference is consistent with the conclusion in the social psychology literature that tourist satisfaction is strongly linked to tourists' perception or subjective feeling (Manning 2003), and thus affects tourists' behavioral intention (Ajzen 1991). Some studies have found that willingness to pay (WTP) is greatly affected by satisfaction (Kang et al 2018), and its stated preference reveals a behavioral intention. This kind of behavioral intention can be re ected by discrete choice modeling, potentially revealing unobservable preference heterogeneity (McFadden and Train 2000).…”
Section: Introductionsupporting
confidence: 89%
See 2 more Smart Citations
“…This inference is consistent with the conclusion in the social psychology literature that tourist satisfaction is strongly linked to tourists' perception or subjective feeling (Manning 2003), and thus affects tourists' behavioral intention (Ajzen 1991). Some studies have found that willingness to pay (WTP) is greatly affected by satisfaction (Kang et al 2018), and its stated preference reveals a behavioral intention. This kind of behavioral intention can be re ected by discrete choice modeling, potentially revealing unobservable preference heterogeneity (McFadden and Train 2000).…”
Section: Introductionsupporting
confidence: 89%
“…Except for the NUM attribute, the higher the tourist satisfaction, the higher the WTP, especially for the BIO attribute. This result partly supports the hypothesis H1 and fully supports H2, which indicates that tourists with higher satisfaction are more inclined to pay more for improving wetland ecotourism than tourists with lower satisfaction (Kang et al 2018).…”
Section: Tourist Satisfaction and Preferencessupporting
confidence: 78%
See 1 more Smart Citation
“…Recreational values refer to the WTP for characteristics found in protected areas such as national parks and nature reserves, which produce a wide range of goods and services that are of merit to tourists (Bennett, 1996). Unfortunately, to date there is not a universally accepted method to effectively monetize the recreational attributes of national parks (Kang et al, 2018). However, two dominant methods have been broadly used in valuing nonmarket resources including recreational resources and activities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…GNP management lacks information on the economic value of the park’s main attributes (De Groot, 1983). Thus, identifying visitors’ preferences toward various park attributes will play a significant role in setting an effective park entrance fee policy (Kang et al, 2018). Setting proper park admission fees is one of the most important instruments for effective park management (Pedersen, 2004), especially for emerging economies (Wilson and Tisdell, 2004).…”
Section: Literature Reviewmentioning
confidence: 99%